Features of teenagers’ deviant behavior - Krainikov, E.; Prokopovich, E.; Zemlyakova, Yu.; Primachenko, S. (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2018)
In order to investigate the problem, we conducted a psychodiagnostic study. During the implementation of the survey, the following tools were used: A. Bass – A. Darkey Questionnaire, Mini-Multifactor Test, Suicidal Risk Questionnaire (T.N. Razuvaeva Modification), Kimberley-Young Internet Addiction Test, Method for determining the tendencies to deviant behavior (A.Orel). The survey was conducted through the written face-to- face group survey of respondents. The resulting data was processed and summarized using statistical processing methods (SPSS v 23). The sample consisted of 78 adolescents (33 boys and 45 girls) aged 15-16 years. According to the results of the analysis, we distinguished two groups of subjects: teenagers with a tendency to deviant behavior and adolescents without such an inclination. Group 1 has included subjects who had high predisposition to the deviant behavior, high rates of aggression, a tendency to Internet addiction, and increased scores of the scale of susceptibility to delinquent behavior. Group 2 has included subjects who did not show the tendency to manifest deviant behavior, and the indicators according to the study were quite low or moderate. Between the indicated groups, differences were shown for a number of indicators. It is stated that adolescents with a high tendency to deviant behavior are characterized by the dominance of emotions over intellectual control in the assessment of situations, affectiveness, disposition to the addictive behavior, computer addiction, as well as high levels of aggression (physical and verbal), feelings of guilt and negativity, demonstration and hypochondria etc. Analyzing the results of the study, we applied the correlation analysis, which revealed the existence of the interconnections between the indicators of "paranoia" with "demonstrativeness" and "uniqueness", as well as between the indicators of aggression and propensity for delinquent behavior.